Arctic Investment Protocol - Guidelines for Responsible Investment in the Arctic - Blom, Anders; Brady, Anne-Marie; Brigham, Lawson; Conley, Heather; Daily, Michael; Hamilton, Neil; Hansen, Rúni M.; Harper, Susan; Henriksen, Sturla; Kamikawa, Yoko; Kortunov, Andrei V.; Minerd, Scott; et al. (2015)
The Arctic is a diverse, rapidly-changing and environmentally sensitive region that is home for its four million residents and also an emerging global investment opportunity. To balance these dimensions, the Investment Protocol of the World Economic Forum Global Agenda Council on the Arctic aspires to promote sustainable and equitable economic growth in the region that furthers community well-being and builds resilient societies in a fair, inclusive and environmentally sound manner.